Analysis of Factors Influencing The Performance of Plantation Workers in The Tlogo Plantation Semarang Regency - Gerardine Widyaswari Pradipta; Wulan Semekar; Bambang Trisetyo Eddy (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
This study aims to analyze the performance of plantation workers and analyze the factors affecting the performance of plantation workers. The research was conducted at Tlogo in Semarang Regency. The research was conducted using survey method. Sampling using simple random sample method. Respondents as many as 50 people from the total population of 123 people. Analyzer using multiple linear regression test. The results showed that 72% of the plantation workers have a moderate production and 68% of the plantation workers have been able to meet the company's work targets. Based on multiple linear regression test, simultaneously got the value of F equal to 3,369, the value is bigger than F table value that is 2,58, so simultaneously, motivation, competence, discipline, and environment influence to plantation workers performance. These factors affect performance by 23%, the rest is influenced by other factors beyond motivation, competence, discipline, and environment. Partial test shows the level of significance of competence, environment, motivation, and discipline respectively is 0.010; 0.114; 0.218; and 0.693. Based on these values indicate that there is a significant influence for competence, while for motivation, discipline, and environment there is no significant effect.